A strategic framework for the optimization of customer relationship management in SMEs - Paraschou, Konstantina (2016)
Customer relationship management (CRM) has been a topic of increased interest during the last decades, for both academics and practitioners. According to the literature review, there has been a variety of scopes and disciplines from which CRM has been addressed. However, CRM in an SME context has been understudied which implies that current literature has been highly driven and shaped by large scale enterprises. This thesis contributes to the examination of the aforementioned research gap. By conducting a single-case study, significant attributes of SME‘s context were analysed and important insights were presented. The aim of this research has been to address CRM from a strategic perspective as a holistic strategic approach to managing and enhancing targeted customer relationships in order to create customer and shareholder value. In this way the full potential of CRM for an organisation can be realized. Two integral parameters have been leading this research, namely, industry and organisational context, as those were identified by the author as key influencers of CRM strategic planning. Furthermore, customer norms and characteristics are encompassed in this research. The findings reveal that a CRM strategy should be organisation specific, context related and strategically aligned with the vision and targets of an organisation. Therefore, understanding and evaluating the current position of an organisation, its internal structure, and its industry norms is the first step to a strategic CRM approach. The proposed strategic framework for CRM emphasises this need for business intelligence and evaluation of the current position before implementing any CRM system. Especially in a fast paced industry where norms imply quick decision making processes and strategic manoeuvring, change management rises as a critical attribute of SMEs. Furthermore, the need for an adaptation period and permeation of fundamental strategic changes among human resources, prior to any radical change in CRM strategy and processes is emphasized by the results of this research.